Increased urinary free immunoglobulin light chain excretion in patients with multiple sclerosis. - Dobson, R; Miller, R; Palmer, H; Feldmann, M; Thompson, E; Thompson, A; Miller, D; Giovannoni, G (2010)
BACKGROUND: Plasma and B cells are implicated in multiple sclerosis (MS) and produce free light chains (FLC) that are excreted in urine. OBJECTIVE: To confirm that demyelinating diseases (DD) cause increased urinary FLCs. METHOD: Urinary FLC in 50 patients with DD were compared to 20 patients with posterior uveitis (PU), 19 with AIDS, 34 with rheumatoid arthritis (RA) and 19 normal controls (NC). RESULT: Subjects with DD, PU, RA and AIDS have higher urinary FLCs than NC (p<0.01). Urinary FLCs did not correlate with gadolinium-enhancing lesions on MRI. CONCLUSIONS: Urinary FLCs are raised in DD. Further studies are required to see if they correlate with disease activity.